(x+9)(x-4)=5x

Simple and best practice solution for (x+9)(x-4)=5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+9)(x-4)=5x equation:



(x+9)(x-4)=5x
We move all terms to the left:
(x+9)(x-4)-(5x)=0
We add all the numbers together, and all the variables
-5x+(x+9)(x-4)=0
We multiply parentheses ..
(+x^2-4x+9x-36)-5x=0
We get rid of parentheses
x^2-4x+9x-5x-36=0
We add all the numbers together, and all the variables
x^2-36=0
a = 1; b = 0; c = -36;
Δ = b2-4ac
Δ = 02-4·1·(-36)
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{144}=12$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-12}{2*1}=\frac{-12}{2} =-6 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+12}{2*1}=\frac{12}{2} =6 $

See similar equations:

| –x–7=–2x–11 | | 0.2(6)+0.04x=0.08(6+x) | | -2/3p-92/5=157/8 | | 5c−c+10=34 | | 6x+8=7x+20 | | 2x-3+1=-7 | | -5/9x+23=-12 | | 10)166=m+97 | | 5-10x=-50 | | 4x-3/24+x=4x+3/4+1 | | -u/2=45 | | 14a-(12a+9)=3/2(12a-18) | | ​3/​2b+5=20−b | | 2.1x+13.755=3-2.91x | | 6k-1+6k=11 | | 3/5x-1/10x=x-2/5 | | ​3​/​2​​b+5=20−b | | 6-1=13x-29 | | (x-5)^(1/2)+2=6 | | 3f+2f+22+8f=204 | | -2x+7=7+-2x | | 12/24=-4/x | | 4^x-6(2^x)=8 | | -5m-2m=-21 | | x+3+8=4 | | -12=-u/6 | | 8g=3g+30 | | 0.5(5−7x)=8−(4x+6) | | 5x-2=40-4 | | 56+19b-15b^2=0 | | 2x+7=7+2x | | 12/42=-4/x |

Equations solver categories